Self-assembly morphology and packing structures depend on the 'head' of organic cations anchored on polyoxometalate anions in hybrids. Issue 9 (2nd September 2017) - Tan, Chunxia; Feng, Ruofei
Abstract: Two organic-polyoxometalates (organic-POMs) hybrids were constructed by fan-shaped 1-methyl-3-[3, 4, 5-tris(octadecyloxy) benzyl]imidazolium salts (labelled as I–Cl) and triethyl-[3, 4, 5-tris (octadecyloxy) benzyl] ammonium salts (labelled as Q–Cl) and Keggin anions [SiW12 O40 ] 4− by electrostatic interaction. Self-assembled behaviours of two aggregates in organic solvent and solid state were investigated in detail by scanning electron microscopy, transmission electron microscopy and X-ray analysis. The mixed solution of chloroform–methanol or chloroform–acetone provided the stable environment for aggregates and aggregates showed a uniform micron size. X-ray analysis results showed that flower-like aggregates morphology of I4 [SiW12 O40 ] based on imidazole ring as 'head' in organic cations was formed by the stacking of multilamellar discs and kept the lamellar structure in solid state. Bulk thorn spheres appeared in Q4 [SiW12 O40 ] aggregates, which were formed by closely interspersed of lots flatted blocks with hexagonal structure characteristics in solid state. The comprehension for the self-assembly morphology and solid structure of organic-polyoxometalate hybrids would help us to use easily modified organic moiety and functional inorganic polyoxoanions as blocks to build novel and giant supramolecular architecture. Abstract :